2022
DOI: 10.1037/pspi0000382
|View full text |Cite
|
Sign up to set email alerts
|

Through the looking glass: A lens-based account of intersectional stereotyping.

Abstract: A growing body of scholarship documents the intersectional nature of social stereotyping, with stereotype content being shaped by a target person's multiple social identities. However, conflicting findings in this literature highlight the need for a broader theoretical integration. For example, although there are contexts in which perceivers stereotype gay Black men and heterosexual Black men in very different ways, so too are there contexts in which perceivers stereotype these men in very similar ways. We dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 119 publications
3
49
0
Order By: Relevance
“…Notably, this argument is similar to one made recently by Petsko et al (2022), according to which intersectional stereotypes are more often observed in contexts where multiple identities of the stereotype targets (vs. just one such identity) are accessible to observers and relevant to their goals. For example, Petsko and colleagues found intersectional stereotypes even in an IAT when participants sorted social stimuli using multiple‐identity labels (e.g., “Black women”) rather than single‐identity labels (e.g., “women”).…”
Section: Discussionsupporting
confidence: 81%
“…Notably, this argument is similar to one made recently by Petsko et al (2022), according to which intersectional stereotypes are more often observed in contexts where multiple identities of the stereotype targets (vs. just one such identity) are accessible to observers and relevant to their goals. For example, Petsko and colleagues found intersectional stereotypes even in an IAT when participants sorted social stimuli using multiple‐identity labels (e.g., “Black women”) rather than single‐identity labels (e.g., “women”).…”
Section: Discussionsupporting
confidence: 81%
“…We also did not find the hypothesized differences between Black men and women for either type of dehumanization; rather, there was no significant difference in the animalistic or mechanistic dehumanization of Black men and women. This result is consistent with Petsko et al's (2022) argument that people use only one lens at a time when evaluating others. In this instance, it appears that a race lens took precedence over a gender or intersectional lens.…”
Section: Implicit Dehumanizationsupporting
confidence: 91%
“…Intersectionality acknowledges that Black women experience discrimination in ways that cannot be explained solely by racism or sexism (Crenshaw, 1989). Petsko et al's (2022) lens-based theory of intersectionality holds that people rely on one "lens" at a time when perceiving others, and that which lens is used depends on the context. In some contexts, people may use a "race" lens, which could lead to discrimination against racial minorities.…”
mentioning
confidence: 99%
“…Second, the stereotypes and emotions assessed in this work were largely assessed in a context-free environment. Research shows that different contexts (e.g., stereotyping in hiring contexts versus criminal sentencing) can elicit different lenses: dependent on situational cues, perceivers may use a religion lens, gender lens, or an intersectional lens when stereotyping groups (Petsko et al, 2022). Future work should examine how changing or specifying context can change these intersectional stereotypes.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%